Community structure of ferns in riparian forest: evaluation in anthropization gradient - Ivanete Teresinha Mallmann; Vinícius Leão da Silva; Jairo Lizandro Schmitt (Revista Ambiente & Água, 2016)
Riparian forests are essential to the maintenance of biodiversity and foster the development of ferns that are indicators of environmental quality. However, these forests have been degraded due mainly to high population density, pattern of urban settlement and agricultural expansion in rural areas. This study evaluated the environmental quality of riparian vegetation of the Cadeia River in Southern Brazil, using phytosociological parameters of the understory’s fern community and a Rapid Assessment Protocol of Habitat Quality (RAPQH). One hundred and twenty plots of 25 m2 were equally distributed among three fragments (FI, FII, FIII). All species of herbaceous ferns were inventoried in each sample unit. We calculated parameters of density, frequency, relative dominance and importance value (IV) of species for the analysis of community structure. The lowest species richness was recorded at FIII (seven species). The floristic composition is more heterogeneous and richness is higher in FI, where the parcels had greater plant cover and RAPQH scores. The RAPQH score decreased with increasing degree of urbanization in the surrounding matrix and FI and FII were classified as “natural,” while FIII was classified as “impacted.” Considering the four species with the highest IV in the three fragments (totaling 69.11% of IV in the FI, 78.36% and 91.06% in FII and FIII respectively), it can be affirmed that the fern community structure is degraded with increasing anthropization.